Good Listening In The Construction Lesson By Ahmed Makki Lazurdi (Rhetorical Analytical Study In Brevity, Circumlocution, And Equality): حسن الإصغاء في درس الإنشاء على تأليف أحمد مكي لازوردي (دراسة تحليلية بلاغية في الإيجاز والإطناب والمساواة) - M. Hari Zakiyudin; Zeiburhanus Saleh (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2021)
This study analyzed the balaghah aspects of the book Husnu al-Ishgo 'fi Dars al-Insya' written by Ahmad Makki Lazuardy that discusses good writing along with essay examples using Arabic methods (ushlub) and a modern vocabulary that is appropriate for sharpens the brains of students or language learners. This study aimed to identify the classifications and types of methods ijaz, ithnab and musawah in that book. This study used qualitative approach with literature review. This study found five ushlub qhasr, seven ushlub ithnab, three al-idah ba'da al-ibham, an al-tikror, and three al-i'tiradh and six ushlub musawah.